Meningkatkan Keterampilan Menulis Geguritan dengan Metode Parallel Writing pada Peserta Didik Kelas X-1 SMA Negeri 3 Yogyakarta - Riris Purbosari (Piwulang Jurnal Pendidikan Bahasa Jawa, 2024)
Writing geguritan is a skill that needs to be mastered by high school level students in Yogyakarta. Even though they are in Yogyakarta, it turns out that Javanese language skills are still an obstacle for students. Javanese language ability influences students' skills in writing geguritan. Students have a limited vocabulary and have difficulty finding inspiration when writing geguritan. This research aims to determine the improvement of geguritan writing skills using the parallelwriting method in class X-1 students at SMA Negeri 3 Yogyakarta. This research is a Classroom Action Research (CAR) model by Kemmis and Mc Taggart. This research uses two cycles. The research procedures that are integrated in each cycle are the planning, action, observation, and reflection stages. The data collection techniques used in this research were tests and non-tests. Based on the research results, it can be seen that the parallelwriting method can improve students' skills in writing geguritan. The average score of students can increase. The average score of students in pre-cycle activities is 64.5, the average score in cycle I is 76, and the average score in cycle II is 77.